Optimal multi-level lot sizing and scheduling with dedicated machines - Alf Kimms (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1994)
This contribution deals with dynamic, capacitated, multi-level lot sizing and scheduling. The basic assumption is that for each item there is exactly one machine that this item can be manufactured on but no two items share a common machine. Finding an optimal solution with a greedy algorithm turns out to be an easy task.
Keywords: 650; Production planning; lot sizing; scheduling; multi-level; dedicated machines; optimal greedy algorithm; Produktionssteuerung; Mathematische Optimierung; Theorie